2015 IEEE Global Engineering Education Conference (EDUCON) 2015
DOI: 10.1109/educon.2015.7096008
|View full text |Cite
|
Sign up to set email alerts
|

First-year dropout in ICT studies

Abstract: There is high demand for qualified Information and Communication Technology (ICT) practitioners in the European labor market. In Estonia, the problem is not a low number of ICT students but a high dropout rate. The aim of this study is to find how it is possible to predict first-year dropout in higher education ICT studies and possibly to engage methods to decrease dropout rate. Data was collected from 301 first-year ICT students in Estonia who filled in a questionnaire at the beginning of the first semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…In addition to programming experience, learning mathematics in school also contributes to success in later IT studies, where mathematics becomes a necessity. The current study revealed that students who scored lower in the mathematics state exam were more likely to drop out in their first study year [2].…”
Section: International Journal Of Information and Education Technologmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition to programming experience, learning mathematics in school also contributes to success in later IT studies, where mathematics becomes a necessity. The current study revealed that students who scored lower in the mathematics state exam were more likely to drop out in their first study year [2].…”
Section: International Journal Of Information and Education Technologmentioning
confidence: 91%
“…who had learned programming before had a higher average grade and considered their studies to be easier than those who first came into contact with programming in their higher education studies [2]. Other studies have also shown that the more programming languages a student has learned, the better he or she performs in tests and exams [34].…”
Section: International Journal Of Information and Education Technologmentioning
confidence: 99%
See 3 more Smart Citations